Evaluation of cardioprotection and bio-efficacy enhancement of stevioside and diltiazem in rats - Laxit Bhatt; Jay Amrutia; Manodeep Chakraborty; Jagadish Kamath (SpringerOpen, 2020)
Abstract Background Cardiovascular diseases and resultant complications of cardio-therapeutic regimens are one of the leading causes of mortalities in developing countries. Diltiazem is a calcium channel blocker primarily used in treatment of supraventricular arrhythmias, systemic hypertension, and hypertrophic cardiomyopathy. Stevioside, the chief component of Stevia plant, is a natural sweetener that has significant therapeutic properties. Stevioside is a known bioenhancer that acts by synergizing pharmacological activities of other drugs. Present study was designed to evaluate cardioprotective activity of stevioside and possible bioenhancement upon co-administration with diltiazem. Standard cardiotoxicity models-isoproterenol-induced myocardial infarction and ischemia-reperfusion injury (IRI) through modified Langendorff setup was used to test this hypothesis. Rats were randomly divided into control groups (normal-physiological saline and toxic-isoproterenol, 150 mg/kg, s.c., and IRI induced in normal control animals) and treatment groups (diltiazem-17.5 mg/kg, p.o., stevioside-100 and 200 mg/kg, p.o. and combination groups). At the end of the treatment period, animals were sacrificed and biochemical, electrocardiographic, and histopathological changes were measured. Results Pre-treatment with stevioside prevented leakage of biomarkers and normalized serum and perfusate levels of CK-MB, CK-NAC, LDH, AST, and ALT enzymes. It displayed lipid-lowering effect on TC and TG levels dose dependently. STV also showed protective action on levels of tissue antioxidant enzymes (SOD and Catalase), electrocardiographic parameters (HR, RR, QRS, QT, PR), and heart tissue histopathology when compared to concurrent toxic control groups. Combination of stevioside (200 mg/kg) and diltiazem (17.5 mg/kg) exerted a more significant pharmacodynamic response, significantly restored biomarkers, antioxidants levels, and myocardial histology, and normalized electrocardiographic parameters. Conclusion Stevioside and diltiazem both displayed cardioprotective effect when given alone. Co-administration displayed improved restorative action on antioxidant status, biomarkers, electrocardiographic parameters, and histology.